Transient enalapril attenuates the reduction in glomerular filtration rate in prenatally programmed rats. Issue 8 (24th April 2017) - Mansuri, Asifhusen; Elmaghrabi, Ayah; Alhamoud, Issa; Legan, Susan K.; Gattineni, Jyothsna; Baum, Michel
Abstract: A maternal low‐protein diet has been shown to program hypertension and a reduction in glomerular filtration rate in adult offspring. This study examined the effect of continuous administration of enalapril in the drinking water and transient administration of enalapril administered from 21 to 42 days of age on blood pressure and glomerular filtration rate (GFR) in male rats whose mothers were fed a 20% protein diet (control) or a 6% protein diet (programmed) during the last half of pregnancy. After birth all rats were fed a 20% protein diet. Programmed rats (maternal 6% protein diet) were hypertensive at 15 months of age compared to control rats and both continuous and transient administration of enalapril had no effect on blood pressure on control offspring, but normalized the blood pressure of programmed offspring. GFR was 3.2 ± 0.1 mL/min in the control group and 1.7 ± 0.1 mL/min in the programmed rats at 17 months of age ( P  < 0.001). The GFR was 3.0 ± 0.1 mL/min in the control and 2.7 ± 0.1 mL/min in the programmed group that received continuous enalapril in their drinking water showing that enalapril can prevent the decrease in GFR in programmed rats. Transient administration of enalapril had no effect on GFR in the control group (3.2 ± 0.1 mL/min) and prevented the decrease in GFR in the programmed group (2.9 ± 0.1 mL/min). In conclusion, transient exposure to enalapril for 3 weeks after weaning can prevent the hypertension and decrease in GFR in prenatal programmed rats. Abstract : This study examined the effect of continuous administration of enalapril in the drinking water and transient administration of enalapril administered from 21 to 42 days of age on blood pressure and glomerular filtration rate (GFR) in male rats whose mothers were fed a 20% protein diet (control) or a 6% protein diet (programmed) during the last half of pregnancy.Transient administration of enalapril had no effect on GFR in the control group and prevented the decrease in GFR in the programmed group. In conclusion, transient exposure to enalapril for 3 weeks after weaning can prevent the hypertension and decrease in GFR in prenatal programmed rats.